The primacy of client privilege: designing a statutory tax advice privilege for accredited non lawyer tax advisors - Wilson-Rogers, Nicole; Morgan, Annette; Pinto, Dale (Taxation Institute of Australia, 2014)
There are several types of professional groups that provide tax advice in Australia: lawyers, accountants, and financial advisors, many of whom are registered tax agents. In many cases, the type of advice provided is the same; however, currently whilst lawyers can extend to their clients a blanket legal professional privilege (“LPP”) over confidential tax advice, clients of non-lawyer tax advisors (“NLTAs”) are presently only granted an administrative concession by the Australian Taxation Office (“ATO”) and then only over a limited range of documents. This article argues in favour of the enactment of a separate statutory tax advice privilege in Australia for accredited NLTAs and suggests a framework for determining which taxation professionals should be able to offer a tax advice privilege to their clients.